The Role of the Seminary in Confronting the Israeli Entity: Ayatollah Sistani and Ayatollah Khamenei as Models: international and political journal - Katea, Assistant lectuer Fuad Karim Khadir (The International and Political Journal, 2025)
This research focuses on the role of religious authority among Shiite Muslims in confronting the Israeli entity, particularly through the issuance of religious fatwas aimed at educating Muslims about the dangers of normalizing relations with the State of Israel and emphasizing the Palestinian cause as a central issue. It also highlights the injustices endured by the Palestinian people, shedding light on the oppression and suffering they face. The study discusses the positions of prominent Shiite authorities worldwide, including Sayyid Ali al-Sistani, the leading figure of the religious seminary in Iraq, and Sayyid Ali Khamenei, the Supreme Leader of the Islamic Republic of Iran.